The effect of age on the clinicopathological features of oral squamous cell carcinoma - Saeed, Alaa S; Abdullah, Bashar H (Journal of Baghdad College of Dentistry, 2022)
Background: Squamous cell carcinoma is a disease of elderly peopleand it is uncommon in people with less than 40 years old; however many literatures revealed that tumor developing in patients younger than forty years appears more aggressive at the time of diagnosis. The purpose of the present study was to focus on the clincopathological features of the oral SCC in different age groups. Material and methods: In this study thirty five cases of paraffin embedded tissue blocks of oral squamous cell carcinoma were studied. The age range was from 16 to 80 years. The clinicopathological data were recorded for evaluating the tumor characters according to age of patients. Results : The age was not significantly correlated to the clinicopathological features that involved the gender of the patients, anatomical site of the tumor, perineural invasion , histological grading and staging .